Dinamika Politik dalam Fit and Proper Test oleh Dewan Perwakilan Rakyat (DPR) dan Implikasinya Terhadap Independensi Hakim Konstitusi - Predderics Hockop Simanjuntak (Universitas Medan Area, 2026)
The independence of constitutional judges is a fundamental prerequisite for ensuring the rule of law and constitutional democracy. However, in Indonesian constitutional practice, the fit and proper test mechanism conducted by the House of Representatives (DPR) often raises debates regarding the extent to which the process is able to guarantee the independence of constitutional judges from the influence of political interests. This study aims to analyze the political dynamics in the fit and proper test mechanism for constitutional judges by the DPR and its implications for the independence of constitutional judges in Indonesia. The study uses a normative legal method with a statutory approach, a conceptual approach, and a case approach. Legal materials are obtained through library studies that include laws and regulations, court decisions, scientific literature, and other supporting documents. The analysis is conducted qualitatively through legal interpretation and review of several cases, namely the dismissal of Constitutional Justice Aswanto, the appointment of Arsul Sani and Adies Kadir as constitutional judges, and the revision of the 2025 Rules of Procedure of the House of Representatives. The results of the study indicate that the political dynamics in the fit and proper test process are not only related to the selection function of prospective judges but also reflect the strong influence of political configurations in filling constitutional judge positions. This situation has implications for the independence of constitutional judges, both institutionally and personally, which can ultimately influence public perception of the Constitutional Court's impartiality. This research proposes strengthening the constitutional merit-based selection system through an independent selection committee, introducing a cooling-off period for active politicians, increasing public participation, and strengthening ethical mechanisms as efforts to strengthen the independence of the judiciary in Indonesia.